Erratum: Measurement of the D*(2010)+ natural linewidth and the D*(2010)+-D0 mass difference - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
[Phys. Rev. D 88, 052003 (2013)] DOI:https://doi.org/10.1103/PhysRevD.88.079902
Im Titel ist das Sternchen "*", das Pluszeichen "+" und die Zahl "0" hochgestellt
The original article was published on 9 September 2013
Gesehen am 23.11.2021